Effect of Synthesis Temperature on Adsorbent Performance of Blending Anionic and Cationic Gels in Divalent Metal Ions Adsorption - Eva Oktavia Ningrum; Suprapto Suprapto; Saidah Altway; Warlinda Eka Triastuti; Afan Hamzah; Agus Surono; Lulu Sekar Taji; Erlangga Ardiansyah (Universitas Gadjah Mada, 2024)
In this study, the anionic and cationic gels were synthesized separately using copolymerization between N-isopropylacrylamide (NIPAM) and acrylic acid or chitosan through a polymerization reaction using N,N'-methylenebisacrylamide (MBAA) as a cross-linker with various monomer concentrations and synthesis temperature. The anionic and cationic gels were blended to minimize inter-intra particle association and to improve the adsorption ability. The FTIR analysis found that the synthesis of the NIPAM-co-acrylic acid and NIPAM-co-chitosan gels was successfully carried out, indicating no presence of a vinyl group in the functional group. The result showed that the ion adsorption amount of Pb2+ ions blending gels increased significantly, almost twice compared to the adsorption before blending. The adsorption amount of Pb2+ ions increased with increasing the gel synthesis temperature. The adsorption amount follows the order of Pb2+ > Fe2+ > Ni2+. The adsorption amount of Pb2+ tends to decrease with increasing sedimentation volume. The higher the synthesis temperature, the larger the porous diameter formed. These results demonstrate that blending gel of NIPAM-co-chitosan and NIPAM-co-acrylic acid is a feasible alternative for removing heavy metal ions owing to its good adsorption performance.